First Semester Students’ Ability in Using Tag Questions at the Faculty of Culture, Management, and Business - Terasne (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to evaluate the ability of first-semester students of the Faculty of Culture, Management, and Business in the academic year 2024/2025 to use question tags in English sentences. A descriptive quantitative method was applied. The instrument used was a 50-item multiple-choice test, each item weighted 2 points. Data analysis employed descriptive statistics to determine average scores, score distribution, and student pass rates. The findings revealed that 72% of the students scored ≥60, indicating a satisfactory mastery of question tag structures. However, 30% of the students still struggled, especially with sentence polarity and the appropriate use of auxiliary verbs. These findings suggest the need for a more contextual and application-based approach in teaching grammar at the university level.